2022
DOI: 10.1002/art.42331
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Gut Microbiome, Metabolome, and Lipidome in Takayasu Arteritis

Abstract: Objective Mounting evidence has linked microbiome and metabolome to systemic autoimmunity and cardiovascular diseases (CVDs). Takayasu arteritis (TAK) is a rare disease that shares features of immune‐related inflammatory diseases and CVDs, about which there is relatively limited information. This study was undertaken to characterize gut microbial dysbiosis and its crosstalk with phenotypes in TAK. Methods To address the discriminatory signatures, we performed shotgun sequencing of fecal metagenome across a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
(83 reference statements)
0
6
3
Order By: Relevance
“…It is generally accepted that the human gut flora consists of about 30 genera and 500 species of bacteria, the microbiota, and that these intestinal players work together to maintain homeostasis in the human gastrointestinal tract (Ling et al, 2022), ensuring the integrity of the epithelial barrier function of the gut and the normal function of various immune cells. Our group has found that dysbiosis of the intestinal flora is associated with many autoimmune diseases, such as primary Sjögren's syndrome (Xin et al, 2022), systemic lupus erythematosus (Yaigoub et al, 2022) and Takayasu arteritis (TA) (Fan et al, 2022). But in this study, our analysis found significantly lower intestinal bacterial abundance and species richness in children with IgAV, KD and IgAN groups than in healthy children, but also a relatively increased number of genera in the different diseases.…”
Section: A B Figurecontrasting
confidence: 65%
“…It is generally accepted that the human gut flora consists of about 30 genera and 500 species of bacteria, the microbiota, and that these intestinal players work together to maintain homeostasis in the human gastrointestinal tract (Ling et al, 2022), ensuring the integrity of the epithelial barrier function of the gut and the normal function of various immune cells. Our group has found that dysbiosis of the intestinal flora is associated with many autoimmune diseases, such as primary Sjögren's syndrome (Xin et al, 2022), systemic lupus erythematosus (Yaigoub et al, 2022) and Takayasu arteritis (TA) (Fan et al, 2022). But in this study, our analysis found significantly lower intestinal bacterial abundance and species richness in children with IgAV, KD and IgAN groups than in healthy children, but also a relatively increased number of genera in the different diseases.…”
Section: A B Figurecontrasting
confidence: 65%
“…The gut microbiota is essential for maintaining healthy immune function, regulating T reg cell activity, and monitoring the processing and presentation of antigens ( 118 ). Immune-related problems, especially autoimmune diseases, may develop if the gut microbial ecology is imbalanced due to poor food, excessive use of antibiotics, or incompetent breastfeeding ( 119 ). Gut microorganisms can regulate specific immune cells and growth factors.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…In contrast to other systemic autoimmune diseases, the impact of gut microbiome in pathogenesis of TAK is not fully understood. In a recent study integrating multi-omics approaches, the authors identified an increased representation of specific bacterial species, such as unclassified Escherichia, Veillonella parvula, Streptococcus parasanguinis, Dorea formicigenerans, Bifidobacterium adolescentis, Lachnospiraceae bacterium 7 1 58FAA, Escherichia coli, Streptococcus salivarius, Klebsiella pneumoniae, Bifidobacterium longum, and Lachnospiraceae Bacterium 5 1 63FAA in patients with TAK compared to healthy controls (41). Interestingly, a significant correlation between microbial metabolites and disease phenotypes, vascular involvement, systemic inflammation, and prognosis was observed, highlighting a potential role for the gut microbiome in the pathogenesis of the disease and providing insights for future research in this field.…”
Section: Therapy Of Lvvmentioning
confidence: 99%